About Lyusternik’s Theorem in Banach Spaces - Aycho Flores, Milton Angelino (2017)
In this article we present to the Lyusternik theorem, used in optimization problems of functional defined in Banach spaces of any dimension, it is also the study of constrained optimization Fr´echet differentiable functional under sufficiently regular conditions.